(untitled) (Journal of the College of Basic Education, 2023)
The information needed by smart environments is provided by Distributed Wireless Sensor Networks, which are responsible for detecting the relevant quantities, monitoring and collecting the data, assessing and evaluating the information, formulating meaningful user displays, and performing decision-making and alarm functions are enormous. The importance of sensor networks is highlighted by the number of recent funding initiatives, including the DARPA SENSIT program, military programs, and NSF Program Announcements. We described the architecture of sensor networks and present the Important features of security in sensor networks , some Types of Attacks on sensor networks and the defense against them finally we propose a public key encryption system by using an algorithm of ElGamal and present the algorithms of encryption , decryption and show the efficiency and security of the proposed system.